Analisis Data Kepuasan Pengguna Layanan E-Wallet Gopay Menggunakan Metode Naïve Bayes Classifier Algorithm - I Gede Iwan Sudipa; I Made Dwi Putra Asana; Ketut Jaya Atmaja; Putu Praba Santika; Dwiki Setiawan (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
E-Wallet or digital wallet is a digital payment instrument using electronic media as a means of payment, in this case, GoPay is one of them. To determine the satisfaction of GoPay digital wallet users in East Denpasar, this research was conducted using the Naïve Bayes Classifier Algorithm method to see how much satisfaction GoPay service users have with GoPay service itself. In collecting data, the researcher used a questionnaire as a data collection method. The data obtained is 100 data, which is divided into two types of datasets, namely training datasets, and testing datasets. The variables used for classification are 2 self-data variables, and 11 question variables based on the attributes that have been used. In determining user satisfaction in this study, researchers used the "Satisfied" class for the satisfied category, and the "Unsatisfied" class for the dissatisfied category. The results obtained from this study are 79 data predictions categorized as satisfied which have the same class as the actual data, 9 prediction data categorized as dissatisfied with the actual data, and test and score which have results AUC 0.995, CA 0.880, F1 0.900, Precision 0.949, Recall 0.880